Strengthening the process of commercialization of technology inventions - Bambang S. Pujantiyo (Faculty of Economics and Business, University of Muhammadiyah Malang, 2022)
The crucial factors for enhancing national competitiveness are the technology readiness of research institutions and the level of industry innovation. The triple helix principle of collaboration between academia, businesses, and government is imperative for successful commercialization of technological inventions. However, this process is not well-established in Indonesia, which necessitates strengthening it to support national competitiveness. This study seeks to reinforce the commercialization process, following Randal Gold Smith's theory, which involves investigation, validation, and commercialization stages. The focus is on strengthening the validation stage, specifically through business model, production, market, and price tests.